Influence of potting mixture on growth and economics of stone graft of mango cv. alphonso - O A Lad (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2020)
Konkan is considered as an important mango belt of India. This belt is not only famous for the production of the king of mango ‘Alphonso’ but also for the supply of quality planting material throughout the country. Soil is the basic medium used in the nursery. Availability of quality soil for nursery is getting scared and it is a need of the hour to find out lightweight, well-aerated media for reducing transport cost and mortality. Hence field experiment was carried out to find the response of mango cv. Alphonso stone grafts in the different potting mixtures. The treatment cocopeat + leaf manure + compost (1:1:2) was recorded significant increase in plant height (129.40%), girth of grafts (38.08%), highest number of shoot (1.50), number of leaf (22.70), highest absolute growth rate (0.1483 cm/day) and relative growth rate (0.0237 cm/cm/day). Whereas, maximum leaf area (617.03 cm2) was obtained in soil + leaf manure (1:1) followed by leaf manure + cocopeat (1:3) (610.17 cm2) leaf manure + cocopeat (1:3). Maximum root length (21.97 cm) and dry weight of root (7.23g) were obtained in treatment cocopeat + leaf manure + compost (1:1:1). The economics involved for different treatments showed that cocopeat + leaf manure + compost (1:1:2) was recorded with the highest B:C (1.39) followed by Soil + Cocopeat (1:1) in stone grafting. From the above investigation, it is concluded that potting mixture had a significant effect on the growth performance and economics of mango grafts. For raising mango grafts, the media containing cocopeat along with leaf manure and compost was the ideal soilless media.